Comprehensive Analysis of Osh Implementation in Community Health Center Based on Permenkes No. 52 of 2018 in Supporting Accreditation Achievement (A Case Study of Padangsari Community Health Center) - Mambe, Sherly (PT. Banjarese Pacific Indonesia, 2024)
Health workers are 1.5 times higher risk of work accidents compared to other professions, with 90% of incidents occurring in developing countries. WHO noted that 3 million out of 35 million health workers are exposed to blood pathogens, increasing the risk of HIV (0.4%), HBV (27-37%), and HCV (3-10%). One of Health center accreditation purpose is to makesure safety to both health workers and patient. In 2023, out of 37 health centers in Semarang, 36 health centers (97.3%) achieved “Plenary” accreditation and 1 Health Center (2.7%) achieved “Main” accreditation. The purpous of this study are to To determine the current OSH practice and determine OSH aspect that needs improvement based on Health Ministry Regulation No.52 of 2018. qualitative methods with a case study design. Occupational Safety and Health (OSH) management at Padangsari Health Center was evaluated based on 92 indicators from three main aspects. In the OHS management criteria, 14 out of 23 indicators (60.9%) have been met. For OSH standards, 45 out of 61 indicators (73.8%) have been met. Meanwhile, 8 indicators related to OSH training, reporting, and recording have all been met. Although Padangsari Health Center has achieved